APLIKASI PEMBUATAN JADWAL PERKULIAHAN DI STIE WIJAYA MULYA SURAKARTA - Kharisma Fajar Renaldi; Astri Charolina (Universitas Sahid Surakarta, 2014)
Lecture Scheduling System STIE Wijaya Mulya Surakarta currently using amanual system in which all of the input data and the scheduling process is done manually so it is less efficient because it requires a relatively long time. Scheduling oflectures conducted by the head of each department of study programs in Accounting and Management. Print schedule of lectures conducted by using Ms. Word. Manuallyscheduling process allows for human error, which can lead to conflicting schedules classes in the absence of validation when scheduling process.The purpose of this study was to develop a system of scheduling lectures there on STIE Wijaya Mulya Surakarta. The system developed is scheduling classes that werepreviously done manually, converted into the form of an application program to be run by the Administration section. This change is necessary in order to simplify, speed upand minimize errors in the process of scheduling lectures are often encountered in scheduling system manually. System development using a structured method. The system is built to match the needs STIE Wijaya Mulya Surakarta. The system is built by using Visual Basic 6.0 andMySQL as the database. The system is equipped with validation in the process of scheduling so as to minimize errors when inputting data or when the schedulingprocess. This system has been tested using blackbox methods and software quality measurement in this study using the method of McCall with the value 78.817%.From the test results, this system is expected to facilitate and expedite the scheduling of lectures that can be applied to STIE Wijaya Mulya Surakarta.